Structural elements of composition design for fabrics image Image footage model (Al-Academy, 2017)
End of the twentieth century witnessed by the technological evolution Convergences between the visual arts aesthetic value and objective representation of the image in the composition of the design of the fabric of new insights and unconventional potential in atypical employment. It is through access to the designs of modern fabrics that address the employment picture footage included several scenes footage from the film, which focuses on research and analytical as a study to demonstrate the elements of the picture and the organization of its rules and how to functioning in the design of fabrics, Thus, it has identified the problem by asking the following: What are the elements of the picture footage and how the functioning of the structural components in the design of fabrics? The aim of the research was "revealed the structural components of the image footage and its role in shaping the design of specific fabrics and functionally." Within the limits of research in the contracts quoted include images from the movie scenes for US films produced 1950_ 1960 and its role in the formation design custom fabrics and functional home furnishings and upholstery and of Turkish origin, produced in 2014. The second chapter the theoretical framework, the first section: the elements of the picture _ the concept, and the second topic: the image technology in the configuration design of the fabric, and the third section: Image and founded the structural design, to describe and analyze models of design fabrics, and reach research into the most important and follows the results:1. directed the picture footage into a coherent sequence to build content start the idea and the continuation of the event and ending scenes, while constructivism content associated with the design fabrics to the content of the idea are fitted regular format based on the formal vocabulary to achieve aesthetic and functional values such as the fabrics for use household upholstery placemats.2. emphasis on influencing shots in movies and choose as Marlin Monroe known figures who were at the center of a fundamental intellectual content and content in frequency came in my intention.3. confirms the correlation between The display mechanism of the image in the artistic film production and design and formulated according to data structural shape, color and values, lighting, movement and performance of the characters, which confirms the vision of producing the film depending on his time and events